Three-dimensional (3D) reconstruction for non-destructive plant growth observation system using close-range photogrammetry method - Arief, M.A.A.; Nugroho, A.P.; Putro, A.W.; Dananta, D.H.; Masithoh, R.E.; Sutiarso, L.; Okayasu, T. (2021)
Agriculture in Indonesia has recently experienced challenges, especially in terms of meeting market demand that tends to increase. Precision agriculture is an effort to increase productivity through optimizing agricultural production processes by minimizing inputs, maximizing output, and reducing the impact on the environment through the use of information and communication technology. Implementation of the concept of precision agriculture is in observing plant growth and development to estimates of plant volume and mass. So far, conventional plant measurements by direct measurement can pose destructive risks to plants. Therefore, a non-destructive system for observing and measuring plants is needed. The purpose of this study was to develop a plant growth observation system based on three-dimensional modelling with non-destructive measurements using the Close-Range Photogrammetry (CRP) method. This system has a 360 orbital scanner component that consists of a frame, camera arm, NEMA 17 stepper motor, Logitech C270 web-camera, Raspberry Pi 3 B +, Adafruit motor driver, and LED strip lights. The stage of image processing using 3DF Zephyr Pro software for generating the 3D sparse point cloud and cropping the unused point. For the validation purposes and its functionality for modelling and estimating volumetric objects, a plant model with three sizes (small, medium, and large) variations were used. As the result, the developed system could observe and model the plant shape in a three-dimensional manner resemble the actual plant model. Â© Published under licence by IOP Publishing Ltd.